ZIF-8-coated PVA / PIL composite antibacterial adsorption film capable of adsorbing dye and metal ions and killing bacteria in wastewater as well as preparation method and application of ZIF-8-coated PVA / PIL composite antibacterial adsorption film

By preparing the ZIF-8@PVA/PIL composite membrane, the problem of existing adsorbents being easily contaminated after long-term operation is solved, and the dyes and metal ions in wastewater are effectively adsorbed, and excellent antibacterial properties are excellent.

CN120132810APending Publication Date: 2025-06-13HENAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510333139.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

Existing adsorbents are susceptible to biological contamination after long-term operation, especially bacterial contamination, making it difficult to efficiently remove organic dyes, metal ions and bacteria in wastewater at the same time.

Method used

A ZIF-8@PVA/PIL composite film was prepared, and a polyionic liquid poly(1-butyl-3-vinyl-1H-imidazole bromide) was obtained by solution polymerization, and then mixed with polyvinyl alcohol (PVA) solution, added zinc nitrate hexahydrate solution, dried in vacuum and soaked in 2-methylimidazole solution, so that ZIF-8 grows in situ on the surface of the membrane to form a ZIF-8@PVA/PIL composite film.

Benefits of technology

This composite membrane can not only efficiently adsorb dyes and metal ions in wastewater, but also has excellent antibacterial properties, which can effectively kill bacteria in wastewater and extend the service life of the adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a ZIF-8 (at) PVA / PIL composite antibacterial adsorption film capable of adsorbing dye and metal ions and killing bacteria in wastewater at the same time. The preparation method comprises the following steps: 1) dispersing 1-vinyl-3-butylimidazolium bromide VBIMBr and azodiisobutyronitrile AIBN in DMF (Dimethyl Formamide), continuously stirring for 12-24 hours at 50-90 DEG C in an inert gas atmosphere, then precipitating in ethyl acetate, and carrying out vacuum drying to obtain PVBIMBr; 2) thermally dissolving polyvinyl alcohol (PVA) in deionized water, and adding the PVBIMBr solution to obtain a PVA / PIL solution; and 3) adding a zinc nitrate hexahydrate solution into the PVA / PIL solution, transferring into a culture dish, carrying out vacuum drying to obtain a thin film, transferring the thin film into a 2-methylimidazole solution, soaking for 12-24 hours to enable ZIF-8 to grow on the surface of the thin film in situ, and carrying out vacuum drying to obtain the zinc nitrate hexahydrate / PVA / PIL composite film. The prepared ZIF-8-coated PVA / PIL composite antibacterial adsorption film can effectively remove bacteria, dyes and metal ions in industrial wastewater, and a new thought is provided for development of multifunctional antibacterial adsorption materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite material for wastewater treatment, and particularly to a preparation method of a composite membrane based on zeolitic imidazolate framework (ZIF-8) and polyvinyl alcohol / polyionic liquid (PVA / PIL) and its application in wastewater treatment, which is particularly suitable for simultaneously removing organic dyes, metal ions and bacteria in wastewater. Background Art

[0002] In recent decades, with the large-scale expansion of industry, water pollution has become a major environmental pollution problem around the world. Due to the recalcitrance of organic dyes and metal ions in industrial wastewater, they accumulate on the earth's surface and in organisms, ultimately leading to ecosystem imbalance, biological deformities and carcinogenicity. Commonly used industrial wastewater treatment methods include catalytic degradation method, electrochemical method, ion exchange method, chemical precipitation method and adsorption method. Among them, the adsorption method has become one of the most effective wastewater treatment methods due to its low cost, high efficiency, wide application range, environmental friendliness and easy large-scale production. However, traditional adsorbents are prone to biological fouling, especially bacterial fouling, after long-term operation. The attachment of microorganisms will significantly shorten the lifespan of the dye adsorbent. Therefore, it is very important to develop an adsorbent for removing industrial wastewater containing bacteria, dyes and metal ions.

[0003] Recently, polyionic liquid-based (PILs) materials have become the highlights in the field of adsorption and attracted more and more attention. Generally speaking, PILs are formed by connecting ionic liquids (ILs) in the repeating units of their polymer chains. The unique properties of functionalized ionic liquids, such as the designable structure, strong polarity, adjustable physical and chemical properties, thermal stability and chemical stability, can therefore be introduced into polyionic liquids to produce polymer materials. So far, PILs have been widely used in catalysis, responsive materials, porous materials, antibacterial properties, adsorption and some energy-related topics. PILs can provide a large number of positive charges, high functional group density and various interactions on adsorbates, such as van der Waals forces, hydrogen bonds, electrostatic interactions and π-π stacking, which make them promising candidates for organic dye adsorbents.

[0004] Zeolitic imidazolate frameworks (ZIFs) are a subclass of metal-organic frameworks (MOFs) and have the same topological structure as the crystals in aluminosilicate zeolites. It is a tetrahedral coordination polymer with a zeolite-like structure, mainly self-assembled from tetracoordinated transition metals such as zinc, cobalt, and imidazole ligands, including 2-methylimidazole and benzimidazole. The most representative ZIF material is ZIF-8 with a zeolite topology (SOD). Based on the advantages of ZIF-8, such as good thermal and chemical stability, high specific surface area, and adjustable framework structure, it is widely used in chemical sensors, adsorption separation, drug delivery, and catalysis. Currently, many studies on adsorbents prepared with ZIF-8 as the carrier can effectively remove dyes and metal ions in wastewater, but they only show high adsorption capacity and removal rate for one kind of pollutant and are difficult to simultaneously meet the requirements of high effective removal rates for different pollutants and bacteria.

[0005] Based on this, this application prepared an efficient, rapid, and synergistic membrane that can adsorb dyes and metal ions while killing bacteria in wastewater. In this study, poly(1-butyl-3-vinyl-1H-imidazolium bromide), a polyionic liquid, was obtained by solution polymerization and then added to a polyvinyl alcohol (PVA) solution to obtain a PIL / PVA film. Then, ZIF-8 was grown in situ on the surface of the composite membrane to form a ZIF-8@PVA / PIL composite membrane. The antibacterial effects of the ZIF-8@PIL / PVA membrane against two common Gram-positive / negative bacteria and two antibiotic-resistant bacteria were systematically studied using the disk diffusion method and colony-forming unit (CFU) method. The mechanical properties, antibacterial effects, and adsorption capacity of the ZIF-8@PVA / PIL membrane were systematically studied to evaluate its application value under different conditions. In addition, the antibacterial mechanism and adsorption mechanism of the ZIF-8@PVA / PIL membrane were further explored. In addition, the preparation of the composite membrane is simple, rapid, convenient, and environmentally friendly. Summary of the Invention

[0006] The object of the present invention is to overcome the defects of the prior art and provide a ZIF-8@PVA / PIL composite antibacterial adsorption membrane that can adsorb dyes and metal ions while killing bacteria in wastewater. This composite membrane can not only efficiently adsorb dyes and metal ions in wastewater but also has excellent antibacterial properties.

[0007] The present invention also provides a preparation method and application of the above-mentioned ZIF-8@PVA / PIL composite antibacterial adsorption membrane that can adsorb dyes and metal ions while killing bacteria in wastewater.

[0008] To achieve the above object, the present invention adopts the following technical solutions: Preparation method of a highly efficient, rapid, and cooperative ZIF-8@PVA / PIL composite antibacterial adsorption membrane capable of adsorbing dyes and metal ions and killing bacteria in wastewater (synthesis route see Figure 1 ) which comprises the following steps: 1) Disperse 1-vinyl-3-butylimidazolium bromide VBIMBr and azobisisobutyronitrile AIBN in DMF (N,N-dimethylformamide), and continuously stir at 50-90 °C for 12-24 hours under an inert gas (such as argon, nitrogen, etc.) atmosphere. Subsequently, precipitate in ethyl acetate and vacuum dry to obtain PVBIMBr poly(1-butyl-3-vinyl-1H-imidazolium bromide); 2) Dissolve polyvinyl alcohol PVA in deionized water by heating, and add the PVBIMBr solution to obtain the PVA / PIL solution; 3) Add zinc nitrate hexahydrate Zn(NO 3 ) 2 ·6H 2 O solution to the PVA / PIL solution, transfer it to a petri dish, vacuum dry to obtain a film, transfer the film to a 2-methylimidazole solution and soak for 12-24 h to in-situ grow ZIF-8 on the film surface, and then vacuum dry to obtain the ZIF-8@PVA / PIL composite antibacterial adsorption membrane. The prepared ZIF-8@PVA / PIL composite antibacterial adsorption membrane can effectively remove bacteria, dyes, and metal ions in industrial wastewater, providing a new idea for the development of multifunctional antibacterial adsorption materials.

[0009] Specifically, in step 1), the mass ratio of 1-vinyl-3-butylimidazolium bromide VBIMBr to AIBN can be 50-100:1. For example, 2 g of VBIMBR and 20 mg of AIBN can be dispersed in 10 mL of DMF.

[0010] Specifically, in step 2), the mass ratio of polyvinyl alcohol to PVBIMBr can be 1-10:1.

[0011] Furthermore, in step 2), polyvinyl alcohol can be heated at 80-120 °C for 0.5-3 h to completely dissolve polyvinyl alcohol in deionized water to form a colorless, transparent, and clear solution.

[0012] Specifically, in step 3), the ratio of zinc nitrate hexahydrate to the sum of the masses of polyvinyl alcohol PVA and PVBIMBr is 5-15:120.

[0013] Furthermore, in step 3), the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 10-30:44-140.

[0014] The present invention provides a ZIF-8@PVA / PIL composite antibacterial adsorption membrane prepared by the above preparation method.

[0015] The present invention also provides an application of the above ZIF-8@PVA / PIL composite antibacterial adsorption membrane in adsorbing dyes and metal ions while killing bacteria in wastewater.

[0016] In the above application, the bacteria include one or more of Escherichia coli, Staphylococcus aureus, kanamycin-resistant Escherichia coli, ampicillin-resistant Escherichia coli, etc. The dyes include methyl orange (MO), congo red (CR), etc., and the metal ions include Cu 2+ etc.

[0017] The application of the ZIF-8@PVA / PIL composite antibacterial adsorption membrane of the present invention in wastewater treatment specifically includes the following steps: placing the composite antibacterial adsorption membrane in wastewater containing dyes and / or metal ions, and removing the dyes and metal ions in the wastewater through adsorption; meanwhile, the ZIF-8 structure on the surface of the composite antibacterial adsorption membrane has excellent antibacterial properties and can effectively kill bacteria in the wastewater.

[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1) The ZIF-8@PVA / PIL composite antibacterial adsorption membrane of the present invention can efficiently adsorb dyes and metal ions in wastewater, has a large adsorption capacity and a high removal efficiency.

[0019] 2) The ZIF-8 structure on the surface of the ZIF-8@PVA / PIL composite antibacterial adsorption membrane of the present invention has excellent antibacterial properties, can effectively kill bacteria in the wastewater, and prolongs the service life of the adsorbent.

[0020] 3) The preparation process of the ZIF-8@PVA / PIL composite antibacterial adsorption membrane of the present invention is simple and fast, the raw materials are easy to obtain, the cost is low, and it is suitable for large-scale industrial production.

[0021] 4) The use of the ZIF-8@PVA / PIL composite antibacterial adsorption membrane of the present invention can reduce the pollution of wastewater to the environment and meet the requirements of environmental protection and sustainable development. Description of the Drawings

[0022] Figure 1 Schematic diagram of the synthesis route of the ZIF-8@PVA / PIL composite material of the present invention and the wastewater treatment process; Figure 2 For PVA (a), PVA / PIL (b) and ZIF-8 in the present invention 0.10 @PVA / PIL (c) surface morphology scanning electron micrograph of the membrane; Figure 3PVA or ZIF-8, PVA / PIL, and ZIF-8 in the present invention 0.10 @FT-IR spectrum (a), Raman spectrum (b), and XRD pattern (c) of the PVA / PIL film Figure 4 ZIF-8 in the present invention 0.10 @Survey scan XPS spectrum (a), N element (b), and Zn element (c) of the PVA / PIL film Figure 5 PVA, PVA / PIL, ZIF-8 0.05 @PVA / PIL, ZIF-8 0.10 @PVA / PIL and ZIF-8 0.15 @Mechanical properties of the PVA / PIL film Figure 6 PVA, PVA / PIL, and ZIF-8 0.10 @Adsorption capacity of the PVA / PIL film for MO (a), CR (b), and Cu 2+ (c) Figure 7 Removal efficiency of different films for MO (a) and Cu 2+ (b), adsorption capacity of MO (c) and Cu 2+ (d) on the ZIF-8 0.10 @PVA / PIL film at different contact times (initial dye concentration = 200 mg / L, initial Cu 2+ concentration = 25 mg / L, adsorbent dosage = 20 mg, solution volume = 50 mL, room temperature); effect of different initial concentrations of MO (e) and Cu 2+ (f) on the adsorption capacity of the ZIF-8 0.10 @PVA / PIL film (initial MO concentration = 25 - 800 mg / L, initial Cu 2+ concentration = 5 - 75 mg / L); effect of different pH values of MO (g) and Cu 2+ (h) on the adsorption capacity of the ZIF-8 0.10 @PVA / PIL film (initial MO concentration = 200 mg / L, initial Cu 2+ concentration = 25 mg / L, pH of MO solution = 3.0 to 11.0, pH of Cu 2+ solution = 2.0 to 6.0) Figure 8 ZIF-8 0.10 @Adsorption of MO and Cu by the ZIF-8 2+Kinetic model fitting, a, c pseudo-first-order model, b, d pseudo-second-order model, and e, f particle diffusion model (initial MO concentration: 200 mg / L, initial Cu 2+ concentration: 25 mg / L); Figure 9 is ZIF-8 0.10 Langmuir isotherm model and Freundlich isotherm model for the adsorption of MO by ZIF-8@PVA / PIL (a - b), MO solution concentration range: 25 - 800 mg / L; ZIF-8 0.10 @PVA / PIL adsorption of Cu 2+ Langmuir isotherm model and Freundlich isotherm model (c - d), Cu 2+ solution concentration range: 5 - 75 mg / L; Figure 10 is the mechanism of ZIF-8@PVA / PIL membrane and its adsorption of anionic dyes MO, CR, and Cu 2+ ; Figure 11 are the optical images of the colonies of common bacteria Staphylococcus aureus and Escherichia coli (a) and two drug-resistant bacteria kanamycin-resistant Escherichia coli and ampicillin-resistant Escherichia coli (b); (c) antibacterial efficiency of ZIF-8@PVA / PIL membrane against Staphylococcus aureus, Escherichia coli, kanamycin-resistant Escherichia coli, and ampicillin-resistant Escherichia coli bacteria; (d) optical images of the inhibition zones of Staphylococcus aureus, Escherichia coli, kanamycin-resistant Escherichia coli, and ampicillin-resistant Escherichia coli bacteria co-cultured with ZIF-8@PVA / PIL membrane for 24 hours after three cycles; (e) inhibition zones of Staphylococcus aureus, Escherichia coli, kanamycin-resistant Escherichia coli, and ampicillin-resistant Escherichia coli bacteria after three cycles; Figure 12 are SEM images of Escherichia coli and Staphylococcus aureus before (a) and after (b) treatment with ZIF-8 0.10 @PVA / PIL; and intracellular components RNA (c), protein leakage (d), and ROS production (e) of Escherichia coli. Detailed implementation manners

[0023] The technical solutions of the present invention will be further introduced in detail below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.

[0024] Example 1 In the following examples, all raw materials used are common commercially available products that can be directly purchased, or can be prepared by conventional techniques in the art.

[0025] Room temperature refers to 25 ± 5 °C.

[0026] Example 1: Preparation of the ZIF-8@PVA / PIL composite antibacterial adsorption membrane (see the synthesis route in Figure 1 ) 1) Preparation of PIL PVBIMBr was synthesized by free radical copolymerization. Specifically, 2 g of VBIMBr and 20 mg of AIBN were dispersed in 10 mL of DMF. The above solution was continuously stirred for 16 hours under an argon atmosphere and at 70 °C. Subsequently, it was precipitated in ethyl acetate and dried in a vacuum oven at 50 °C for 12 hours to obtain purified PVBIMBr.

[0027] 2) Preparation of PVA / PIL First, 1 g of polyvinyl alcohol PVA was added to 10 mL of deionized water and heated at 90 °C for 2 h to completely dissolve the polyvinyl alcohol, forming a colorless, transparent and clear solution. Subsequently, 2 mL of a 100 mg / mL PVBIMBr solution was added to the above PVA solution to obtain a PVA / PIL solution.

[0028] 3) Preparation of ZIF-8@PVA / PIL 5 mL of Zn(NO 3 ) 2 ·6H 2 O solutions (concentrations of 10, 20, and 30 mg / mL) were respectively added to the above-obtained PVA / PIL solutions, and then transferred to a glass petri dish and vacuum dried at 60 °C for 12 h to obtain a film. Subsequently, the film was soaked in 20 mL of 2-methylimidazole solutions with different concentrations (11.57, 23.14, 34.71 mg / ml) for 24 h to enable in-situ growth of ZIF-8 on the film surface. With the completion of the in-situ growth of ZIF-8, the above mixed solution was poured into a mold and vacuum dried at 60 °C to form a film, namely, the ZIF-8@PVA / PIL composite antibacterial adsorption membrane. According to the mass of Zn(NO 3 ) 2 ·6H 2 O, these membranes were respectively named ZIF-8 0.05 @PVA / PIL, ZIF-8 0.10 @PVA / PIL, and ZIF-8 0.15 @PVA / PIL.

[0029] Meanwhile, for comparison, the preparation of the PVA / PIL composite membrane was given: Referring to the above steps 1) and 2), a PVA / PIL solution was prepared, then heated and stirred at 70 °C for 2 h, and finally the above mixed solution was poured into a glass petri dish and vacuum dried at 60 °C for 12 h to form a film, obtaining the PVA / PIL composite membrane.

[0030] Example 2: Characterization of Materials The morphologies of PVA, PVA / PIL, and ZIF-8@PVA / PIL membranes were observed by scanning electron microscopy, and the results are shown in 0.10 . Figure 2 . Figure 2 As shown in a and b, the morphologies of PVA and PVA / PIL are dense and smooth. After in-situ growth of ZIF-8, a large number of hexagonal crystals appear on the membrane surface in Figure 2 c, which confirms the successful anchoring of ZIF-8 on PVA / PIL.

[0031] To determine the structure and chemical composition of ZIF-8@PVA / PIL, infrared spectroscopy and Raman spectroscopy were used to study it. As 0.10 shown in a, PVA exhibits typical -CH asymmetric and symmetric stretching vibration bands at 2941 cm Figure 3 . The peaks at 3296 cm -1 , 1650 cm 2 , and 1207 cm -1 are attributed to the stretching bands of -OH, -CH, and C=O, respectively. In the PVA / PIL film, the stretching vibration of C-C becomes larger at the peak of 750 to 882 cm -1 due to the hydrogen bonding between PIL and PVA. In addition, the new peak at 1553 cm -1 is attributed to the characteristic peak of the imidazole ring. Moreover, in the FT-IR spectrum of ZIF-8@PVA / PIL, the peak at 1553 cm -1 is enhanced, and the peaks at 748 and 439 cm -1 correspond to the stretching vibrations of ν(Zn-N) and ν(Zn-O), which verifies the presence of ZIF-8 on the PVA / PIL film. In the Raman spectrum of ZIF-8, three characteristic sharp peaks appear at 686, 1146, and 1458 cm 0.10 in -1 b. At the same time, in the Raman spectrum of ZIF-8@PVA / PIL, the peaks at 680, 1138, and 1451 cm -1 are blue-shifted, indicating a slight deformation of the ZIF-8 lattice. Therefore, these results prove the successful preparation of ZIF-8@PVA / PIL. Figure 3 As shown in -1 c, the synthesized ZIF-8, PVA, and ZIF-8@PVA / PIL were studied by XRD 0.10 -1 .

[0032] As Figure 3 shown in 0.10 ​@Crystal structure and phase purity of PVA / PIL. The characteristic peaks of ZIF-8 appear at 10.9º (002), 13.2º (112), 15.3º (022), 16.8º (013), 18.6º (222), 23.9º (233), 25.1º (002), 26.2º (134), and 27.2º (002), respectively, which correspond to the porous structure of ZIF-8, indicating the successful preparation of ZIF-8. PVA shows a broad peak at 19.8 (101), which corresponds to the semi-crystalline structure. In addition, ZIF-8 0.10 @PVA / PIL shows the same characteristic peaks as pure ZIF-8 (2θ = 17.1, 18.31, 22.5, 28.25, and 29.1), indicating the presence of the ZIF-8 crystal structure in the composite membrane and proving the successful in-situ growth of ZIF-8 in the membrane.

[0033] In addition, the detailed binding energy and chemical composition of ZIF-8 0.10 @PVA / PIL were studied by XPS. ZIF-8 0.10 @The full-scan XPS spectrum of PVA / PIL ( Figure 4 a) shows that the main elements include C, N, O, and Zn. As shown in Figure 4 a, the N 1s spectrum of ZIF-8 0.10 @PVA / PIL has two peaks at 400.2 and 398.4 eV, which are attributed to N-H and N-C bonds. In addition, the peaks at 1044.8 and 1021.7 eV correspond to Zn 2p 1 / 2 and Zn 2p 3 / 2, respectively, as shown in Figure 4 c, proving that the ZIF-8 component was successfully loaded on the composite membrane. Therefore, the characterization results show that ZIF-8 0.10 @PVA / PIL was successfully prepared in this application.

[0034] Example 3: Mechanical properties The mechanical properties of the prepared membranes were studied in this application, and the results are as shown in Figure 5 and Table 1. It can be seen from the results of Figure 5 and Table 1 that the PVA / PIL composite membrane shows a tensile strength of 27.8 MPa and an elongation at break of 151.02%, both of which are higher than those of the original PVA membrane due to the hydrogen bond between the -OH group and the imidazole ring. With the increase in the ZIF-8 content, the elongation of the composite membrane shows a trend of first increasing and then decreasing, which is attributed to the plasticizing effect of ZIF-8. It should be noted that although the tensile strength of the ZIF-8 1.0 @PVA / PIL thin film decreases slightly, the elongation of the ZIF-8 1.0 @PVA / PIL thin film is significantly higher than that of the pure PVA and PVA / PIL thin films.

[0035] Table 1 Mechanical properties of PVA, PVA / PIL, and ZIF-8@PVA / PIL films Example 4: Adsorption evaluation of ZIF-8@PVA / PIL film To evaluate the adsorption capacity of different films for harmful pollutants such as MO, CR, and Cu 2+ , relevant adsorption tests were conducted in this application, and the results are shown in Figure 6 . Figure 6 a - c show the effect of contact time in the film adsorbent on the removal capacity of organic pollutants (initial concentration MO: 100 mg / L, CR: 100 mg / L, Cu 2+ 20 mg / L). In the initial 0 - 5 minutes, a rapid and significant removal effect on MO, CR, and Cu 2+ can be clearly observed, and then the removal process gradually reaches a dynamic adsorption equilibrium. Using 20 mg of ZIF-8 0.10 @PVA / PIL film as the adsorbent, the adsorption of MO, CR, and Cu 2+ reaches equilibrium at 9 minutes, and the adsorption rates are 93.1%, 94.4%, and 80.7% respectively.

[0036] In addition,[[]] Figure 7 a - b studied the adsorption capacity of different contents of ZIF-8 for MO and Cu 2+ (initial concentration MO: 200 mg / L and Cu 2+ 25 mg / L). Figure 7 a shows that the adsorption rates of PVA, PVA / PIL, ZIF-8 0.05 @PVA / PIL, ZIF-8 0.10 @PVA / PIL, and ZIF-8 0.15 @PVA / PIL for methyl orange MO are 1.39%, 69.7%, 85.7%, 91.1%, and 87.2% respectively. As Figure 7 shown in b, the adsorption rates of Cu 2+ are 1.17%, 1.45%, 76.7%, 78.9%, and 80.1% respectively. After loading the ZIF-8 component, the adsorption amount of ZIF-8@PVA / PIL increases, especially for the adsorption amount of Cu 2+ .

[0037] On the basis of exploring different adsorbents, the effects of different contact times, initial concentrations, and pH values on the adsorption performance of ZIF-8 0.10 @PVA / PIL were studied. From 0 - 20 minutes, the ZIF-8 0.10Removal efficiency of PVA / PIL for MO and Cu 2+ as a function of contact time is shown in Figure 7 c and d. For methyl orange adsorption, due to the abundance of functional sites in the thin film, the adsorption initially increases rapidly, promoting rapid electrostatic binding with negatively charged dye molecules. The percentage of anionic dye removal increases significantly with time and reaches 91.08% at 10 minutes. After about 10 minutes, the adsorption tends to stabilize, indicating that the active sites of dye molecules are saturated due to electrostatic interactions, and the adsorption rate reaches 92.59% at 20 minutes. At the same time, the adsorption amount of Cu 2+ gradually reaches equilibrium around 12 min, and the adsorption efficiency reaches 81.45% at 20 min, showing a similar trend. As shown in Figure 7 e, the initial concentration of MO is adjusted to 25, 50, 75, 100, 200, 400, and 800 mg / L respectively. The results show that with the increase of the initial concentration of MO, the removal amount of MO generally increases gradually, which is due to the increase of the active sites in contact with MO on the membrane as the initial concentration of MO increases. However, when the initial MO concentration is 800 mg / L, the removal amount reaches equilibrium, which may be due to the limited adsorption sites on the membrane surface. At the same time, the adsorption of Cu 2+ shows a similar trend at 5, 10, 15, 20, 25, 50, and 75 mg / L, as shown in Figure 7 d. This is attributed to the abundant active sites provided by the hierarchical pore structure of the material. As the metal ions in the solution increase, more active sites on the composite membrane come into contact with the metal ions. However, after the concentration exceeds the critical value, the adsorption sites on the adsorption membrane are gradually completely occupied, and the metal ions on the surface of the composite membrane repel the metal ions in the solution, competing with the site saturation effect, resulting in a decrease in adsorption efficiency. In addition, the maximum adsorption amounts of ZIF-8 0.10 @PVA / PIL for MO and Cu 2+ reach 684.1 mg / g and 68.9 mg / g respectively.

[0038] In addition, to study the effect of pH value, 20 mg of ZIF-8 0.10 @PVA / PIL was immersed in 50 mL of MO (200 mg / L) and Cu 2+ (25 mg / L) solutions, and the pH value of the MO solution was adjusted from 3 to 11 and that of the Cu 2+ solution was adjusted from 2 to 6 with 0.1 mol / L HCl or 0.1 mol / L NaOH respectively. As shown in Figure 7 e and f, the removal efficiency of ZIF-8 0.10 @PVA / PIL for MO and Cu 2+ at different pH values was studied.Figure 7 e shows that as the pH value increases, the adsorption efficiency of MO decreases from 92.47% (467.4 mg / g) at pH = 3 to 80.75% (413.61 mg / g) at pH = 11. This reduction is attributed to the increased protonation of carboxyl groups at lower pH levels, resulting in a higher positive charge density on the film surface, which promotes stronger electrostatic attraction with negatively charged dye molecules. At higher pH levels, the reduced positive charge on the membrane surface weakens this attraction, leading to lower adsorption capacity. From Figure 7 f, it can be seen that from pH = 2 to pH = 6, the adsorption capacity of Cu 2+ gradually increases. When the pH is 6, the adsorption amount reaches a maximum of 49.480 mg / g (80.17%), which may be due to the increased surface charge of the ZIF-8 0.10 @PVA / PIL membrane at pH values of 2 - 6, thus improving the binding ability with Cu(ii). When the pH value is above 6, the concentration of OH - increases, and OH - must combine with Cu(ii) to form insoluble Cu(OH) 2 , thus affecting the experimental results.

[0039] In addition, we also compared the adsorption capacities of other adsorbents for MO and Cu 2+ . As shown in Tables 2 and 3. The adsorption capacity of the ZIF-8@PVA / PIL membrane in this study is significantly higher than that of other adsorbents reported in previous studies, highlighting their potential as efficient adsorbents. This increased adsorption capacity of the ZIF-8@PVA / PIL membrane is attributed to the large number of cationic charges on the PIL surface and the in-situ growth of ZIF-8, highlighting their potential in applications requiring effective removal of anionic dyes and Cu 2+ from wastewater.

[0040] Table 2 Comparison with other existing adsorbents for the adsorption of methyl orange MO Table 3 Comparison with other existing adsorbents for the adsorption of Cu 2+ Example 5: Adsorption mechanism of ZIF-8 @ polyvinyl alcohol / PIL membrane To further investigate the adsorption of MO and Cu 0.10 by ZIF-8 2+ @PVA / PIL, the adsorption data of MO (200 mg / L) and Cu 2+ (25 mg / L) solutions were fitted with the pseudo-first-order, pseudo-second-order adsorption kinetics and intraparticle diffusion models. Figure 8 ​a and b show ZIF-8 0.10 @Pseudo-first-order (PFO) and pseudo-second-order (PSO) adsorption kinetics of MO by PVA / PIL, where ZIF-8 0.10 @The PFO of PVA / PIL (R 2 = 0.9949) is higher than that of PSO (R 2 = 0.9881), indicating that physical adsorption dominates the adsorption process of MO by the material. At the same time, as Figure 8 shown in c and d, chemisorption dominates in the Cu 2+ adsorption experiment, because the PSO of the kinetic model (R 2 = 0.9965) is higher than that of PFO (R 2 = 0.9890). Figure 8 e and f show ZIF-8 0.10 @PVA / PIL adsorption of MO and Cu 2+ intraparticle diffusion kinetics. The first stage of ZIF-8 0.10 @PVA / PIL adsorption of MO belongs to the surface diffusion of the adsorbent. There are a large number of adsorption sites on the surface of the adsorbent, and MO rapidly diffuses from the solution to the outer surface of the adsorbent. Therefore, the first stage is a rapid adsorption process; the second stage belongs to the intrapore diffusion stage of the adsorbent, and the transfer of MO and Cu 2+ on the surface of the adsorbent slows down, the sites on the surface of the adsorbent are gradually occupied, and the adsorption rate gradually decreases. The third stage belongs to the micropore diffusion stage of adsorption. The sites on the surface of the adsorbent are gradually completely occupied, and the MO molecules on the surface of ZIF-8 0.10 @PVA / PIL repel the MO molecules in the solution, and the adsorption process of ZIF-8 1.0 @PVA / PIL for MO tends to reach an equilibrium state. At the same time, ZIF-8 0.10 @PVA / PIL has the same trend in the process of adsorbing Cu 2+ , and the adsorption rate is controlled by intraparticle diffusion.

[0041] In addition, the Langmuir and Freundlich models were used to fit the relationship between the adsorption capacity of the material and the concentrations of MO and Cu 2+ . The results are shown in Figure 9 . Compared with the Freundlich adsorption model ( Figure 9 b and d), the Langmuir adsorption models ( 2+ a and c) for adsorbing MO and Cu Figure 9 have the highest correlation coefficients (R 2 = 0.9970 and R 2 = 0.9939). The results verify that ZIF-8 0.10 @PVA / PIL membrane for MO and Cu2+ The adsorption is monolayer adsorption, and the adsorption sites of the material are evenly distributed on the surface.

[0042] The materials for anionic dyes MO, CR and Cu 2+ The possible adsorption mechanism is as Figure 10 shown. The adsorption kinetics and isotherm results show that the adsorption of anionic dyes and Cu 2+ is mainly a physical adsorption and a chemical adsorption process respectively, controlled by surface diffusion. In addition, anionic dyes mainly exist in the anionic form in solution, the material surface is rich in cations, and there is an electrostatic attraction between anionic dyes and the ZIF-8@PVA / PIL film, which is the main regulation mechanism for the adsorption of anionic dyes. In addition, due to the presence of aromatic rings in MO and CR molecules, the π-π interaction effect may contribute to the adsorption of the material. The surface of the composite film has metal coordination sites (i.e., nitrogen atoms in imidazolium salts) in its pore structure, which are prone to form coordination with Cu 2+ , which may be attributed to the diffusion of solution molecules into coordination bonds for Cu 2+ , thus providing a basis for the capture and adsorption of Cu 2+ inside ZIF-8. In addition, the ionic radii of Cu 2+ and Zn 2+ are similar, and Cu 2+ can replace Zn 2+ in ZIF-8 and be embedded in its structure, indicating that the process of removing Cu(II) by ZIF-8 may involve an ion exchange reaction by destroying the ZIF-8 framework. In summary, the adsorption process of anionic dyes by the ZIF-8@PVA / PIL film involves π-π interaction and electrostatic interaction, and ion exchange is the main mechanism for the Cu 2+ adsorption process.

[0043] Example 6: Antibacterial activity The antibacterial activities of PVA, PVA / PIL, and ZIF-8 0.10 @PVA / PIL were studied by the CFU colony forming unit method. The antibacterial efficiencies of PVA, PVA / PIL, and ZIF-8 0.10 @PVA / PIL at different culture times (0, 15, 30, and 60 minutes) are shown in Figure 11 a-c. As Figure 11 shown in a and c, PVA has no antibacterial activity within 0-60 minutes. In contrast, PVA / PIL and ZIF-8 0.10 @PVA / PIL reached 100% bactericidal efficiency against Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) bacteria respectively within 30 minutes. On the other hand, compared with PVA / PIL, ZIF-8 0.10@PVA / PIL shows excellent bactericidal ability against kanamycin-resistant Escherichia coli (Kanamycin-resistant E. coli ), and penicillin-resistant Escherichia coli (Penicillin-resistant E. coli ). As shown in Figure 11 b and c, ZIF-8 0.10 @PVA / PIL shows an antibacterial efficiency of 91.2% in only 15 minutes and achieves complete eradication of all bacteria of kanamycin-resistant Escherichia coli after 30 minutes. Meanwhile, ZIF-8 0.10 @PVA / PIL shows antibacterial efficiencies of 3.1%, 90.2%, 100% and 100% at 0, 15, 30 and 60 minutes respectively in the experiment with penicillin-resistant Escherichia coli. In contrast, PVA / PIL shows a moderate effect on drug-resistant bacteria, with antibacterial efficiencies of only 37.41% and 41.34% against kanamycin-resistant Escherichia coli and penicillin-resistant Escherichia coli bacteria respectively at 15 minutes. Therefore, the synergistic effect of PVA / PIL and ZIF-8 0.10 in ZIF-8@PVA / PIL may effectively kill drug-resistant bacteria. The above results indicate that ZIF-8 0.10 @PVA / PIL membrane has excellent antibacterial performance.

[0044] In addition, the antibacterial cycle of ZIF-8 0.10 @PVA / PIL membrane was further studied by the agar diffusion method. The optical images of Escherichia coli, Staphylococcus aureus, kanamycin-resistant Escherichia coli and penicillin-resistant Escherichia coli bacteria co-cultured with ZIF-8 0.10 @PVA / PIL membrane for 24 hours are shown in Figure 11 d and e. It can be clearly seen from the figure that in the first experiment, there is a clear inhibition zone around the ZIF-8 0.10 @PVA / PIL membrane. In the second and third cycle experiments, the ZIF-8 0.10 @PVA / PIL thin film still shows a clear and obvious inhibition zone on the top of the culture dish. Therefore, these results further indicate that the prepared membrane has good recyclability, which provides theoretical support for its potential use in water treatment.

[0045] To better explore the antibacterial mechanism of ZIF-8 0.10 @PVA / PIL thin film, scanning electron microscopy was used to study the changes in the front and back surfaces and morphological structures of bacteria before and after exposure to the prepared thin film. In Figure 12 a, the morphologies of untreated Escherichia coli and Staphylococcus aureus bacteria are clearly intact. Meanwhile, after exposure to ZIF-80.10 SEM of bacteria after @PVA / PIL film( Figure 12 b) shows the most severe atrophy and damage of the bacterial membrane. The results indicate that ZIF-8 0.10 @PVA / PIL film caused damage to the bacterial morphology, which may be one of the main reasons for ZIF-8 0.10 @PVA / PIL film to inhibit pathogenic bacteria. The results show that the composite film caused severe damage to the surface morphology of bacteria, leading to the death of pathogenic bacteria.

[0046] The loss of intracellular RNA (ribonucleic acid), proteins, and nucleic acids in bacteria was further used to measure the integrity of the bacterial cell membrane. As Figure 12 shown in c, the content of RNA in the Escherichia coli suspension of ZIF-8 0.10 @PVA / PIL after treatment was significantly higher than that of the control group. In addition, the rupture of the bacterial cell membrane would lead to the release of cell nutrients, so the experiment was carried out with the protein leakage amount as an index. Figure 12 d shows that the protein leakage in the Escherichia coli suspension exposed to ZIF-8 0.10 @PVA / PIL was significantly higher than that of the control group. The leakage of a larger amount of RNA and proteins indicates that ZIF-8 0.10 @PVA / PIL film has outstanding antibacterial properties by destroying the integrity of the bacterial cell membrane, which may promote the permeability of the bacterial membrane and lead to a high release content of bacterial RNA and protein components.

[0047] In addition to the direct physical contact between the film and bacterial cells, the loss of intracellular components, and the destruction of the structural integrity of bacteria, the oxidative stress response is another important antibacterial mechanism. A recent study has demonstrated that the accumulation of a high content of ROS can lead to a higher level of oxidative stress in bacterial cells, resulting in severe damage to the bacterial cell membrane, intracellular DNA, and protein components. Since the oxidative stress response caused by the accumulation of ROS content can be measured by a quantitative detection method. Under normal environmental and balanced conditions, the content of ROS is considered a by-product of the metabolic process and plays a rather important role in bacterial cell homeostasis, which may be disrupted by the external environment. As Figure 12 shown in e, the ROS level in the experimental group was significantly higher than that of the control group, and the ROS content of ZIF-8 0.10 @PVA / PIL increased by 611.93% compared with the control group. Therefore, the research results indicate that the death of bacteria may be due to ZIF-8 0.10 @PVA / PIL film releasing Zn 2+ into the bacteria, which subsequently induced an increase in the level of oxidative stress.

Claims

1. A method for preparing a ZIF-8@PVA / PIL composite antibacterial adsorption membrane that absorbs dyes and metal ions and kills bacteria in wastewater, characterized in that: The steps include: 1) Disperse 1-vinyl-3-butylimidazolium bromide VBIMBr and azobisisobutyronitrile AIBN in DMF, stir continuously at 50-90°C for 12-24 hours under an inert gas atmosphere, then precipitate in ethyl acetate, and vacuum dry to obtain PVBIMBr; 2) Heat dissolving polyvinyl alcohol (PVA) in deionized water, adding PVBIMBr solution to obtain PVA / PIL solution; 3) Add zinc nitrate hexahydrate solution to the PVA / PIL solution, transfer to a culture dish, and vacuum dry to obtain a film. Transfer the film to a 2-methylimidazole solution and soak for 12-24 h to allow ZIF-8 to grow in situ on the film surface. Vacuum dry to obtain the film.

2. The method for preparing the ZIF-8@PVA / PIL composite antibacterial adsorption film according to claim 1, characterized in that: In step 1), the mass ratio of 1-vinyl-3-butylimidazolium bromide VBIMBr to azobisisobutyronitrile AIBN is 50-100:

1.

3. The method for preparing the ZIF-8@PVA / PIL composite antibacterial adsorption membrane according to claim 1, characterized in that: In step 2), the mass ratio of polyvinyl alcohol to PVBIMBr is 1-10:

1.

4. The method for preparing the ZIF-8@PVA / PIL composite antibacterial adsorption film according to claim 1, characterized in that: In step 2), polyvinyl alcohol is heated at 80-120° C. for 0.5-3 h to be thermally dissolved in deionized water.

5. The method for preparing the ZIF-8@PVA / PIL composite antibacterial adsorption film according to claim 1, characterized in that: In step 3), the ratio of zinc nitrate hexahydrate to the sum of the mass of polyvinyl alcohol PVA and PVBIMBr is 5-15:

120.

6. The method for preparing the ZIF-8@PVA / PIL composite antibacterial adsorption membrane according to claim 1, characterized in that: In step 3), the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 10-30:44-140.

7. The ZIF-8@PVA / PIL composite antibacterial adsorption membrane prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the ZIF-8@PVA / PIL composite antibacterial adsorption membrane described in claim 7 in the adsorption of dyes and metal ions while killing bacteria in wastewater.

9. The use according to claim 8, characterized in that The bacteria include one or more of Escherichia coli, Staphylococcus aureus, kanamycin-resistant Escherichia coli and ampicillin-resistant Escherichia coli bacteria.

10. The use according to claim 8, characterized in that The dyes include methyl orange and Congo red, and the metal ions include Cu 2+ .